Genetic polymorphisms of bone marrow stromal cell antigen-1 (BST-1/CD157): implications for immune/inflammatory dysfunction in neuropsychiatric disorders - Yokoyama, Shigeru (Frontiers in Immunology, 2023)
Bone marrow stromal cell antigen-1 (BST-1/CD157) an immune/inflammatory regulator that functions as both nicotinamide adenine dinucleotide-metabolizing ectoenzyme and cell-surface signaling receptor. BST-1/CD157 is expressed not only in peripheral tissues, but in the central nervous system (CNS). Although its pathophysiological significance in the CNS is still unclear, clinical genetic studies over a decade have begun revealing relationships between BST-1/CD157 and neuropsychiatric diseases including Parkinson’s disease, autism spectrum disorders, sleep disorders, depressive disorders and restless leg syndrome. This review summarizes the accumulating evidence for the involvement of BST-1/CD157 in these disorders.